Rhetorical Miracles in the Vocabulary of Quranic Composition Surah Al-Ikhlas as a Model - Alsaied, Mohamad Abdullah (Journal of Ecohumanism, 2024)
This research aims to uncover the facets of rhetorical miracles in the vocabulary of one of the chapters of the Holy Quran, specifically Surah (Al-Ikhlas). This surah is among the shorter chapters that encapsulate matters of faith and numerous benefits through magnificent and high-level rhetorical forms. This is because the Holy Quran, which is concise and succinct in its words, verses, and chapters, possesses all aspects of eloquence in their various forms comprehensively and entirely ranging from clarity and literary beauty to profound meanings all interconnected without any fragmentation or flaw. This invites us to observe these facets in the vocabulary of this noble Quranic surah, highlighting its high status and elevated position similar to other great chapters of the Quran and its profound sanctity. This is because it is the miraculous word of God in its expression and clarity, and its noble meanings. All of this falls under a type of thematic interpretation in its rhetorical form, presented in a concise manner, carrying many subtle details of Quranic meanings, hinted at through the composition of words and the structure of terms, in an eloquent manner found only in the Great Quran.